Hypocarnitinemia and its effect on seizure control in adult patients with intractable epilepsy on the modified Atkins diet - Chu, Daniel Y.; Ravelli, Michele N.; Faltersack, Kelly M.; Woods, Arron L.; Almane, Dace; Li, Zhanhai; Sampene, Emmanuel; Felton, Elizabeth A. (Frontiers in Nutrition, 2024)
Introduction: Previous studies have demonstrated the safety and efficacy of the modified Atkins diet (MAD) in attenuating seizures in patients with intractable epilepsy. MAD works by achieving ketosis, which is heavily dependent on the metabolic compound, carnitine, to facilitate the transport of longchain fatty acids across the mitochondria for beta-oxidation. The effect of carnitine on ketogenic diet therapy is not well-defined in the current literature. Thus, the purpose of our study is to investigate the effects of hypocarnitinemia on the efficacy of MAD.Methods: A retrospective chart review was conducted, and 58 adults with epilepsy undergoing MAD were evaluated. Generalized linear mixed effects models were used to compare the low carnitine status with normal carnitine group in patient measures of body mass index, seizure frequency and severity, number of anti-seizure medications, beta-hydroxybutyrate, triglyceride, and carnitine levels across baseline, 3-9-month follow-up (timepoint 1), 1-2-year follow-up (timepoint 2), and 2+ year follow-up (timepoint 3).Results: Our study revealed that 38.3% of adult patients with epilepsy following MAD experienced low free carnitine at some point through the course of diet therapy. Patients with hypocarnitinemia at timepoint 2 showed a significant percent seizure increase while seizures continued to decrease in the normal carnitine group. Fasting triglyceride levels at timepoint 1 were significantly increased in the low carnitine group compared to normal carnitine group. Change in BHB, BMI, seizure severity, and number of ASMs showcased no significant differences between the low and normal carnitine groups.Discussion: It may be important for clinicians to monitor for hypocarnitinemia in adults on MAD and provide carnitine supplementation when low. Further investigations into carnitine and MAD may inform clinical decisions on carnitine supplementation to maximize the efficacy of MAD therapy.